Perencanaan Angkutan Feeder (Rute Terminal Joyoboyo – Terminal Osowilangon) - Putra, Dwi Setiawan; Utomo, Nugroho; Fatikasari, Aulia Dewi (Jurnal Talenta Sipil, 2025)
Intermodal transportation embodies dynamic individual journeys as passengers transition by involving multiple transportation modes in one trip at multiple transportation node points. Feeder transportation is a means of transportation that provides facilities to all communities so that they can reach residential areas and commercial sectors in urban areas. Feeder transportation planning research aims to determine the socio-economic characteristics and travel characteristics of respondents which influence feeder transportation planning. Knowing the number and location of shelters in feeder transportation planning and knowing the number of fleets in feeder transportation planning, especially on the Joyoboyo Terminal - Osowilangon Terminal route. The method applied in this study was to provide questionnaires to several visitors to the Joyoboyo Terminal and Osowilangon Terminal with questions that had been compiled using the stated preference method. Determining the number and location of shelters referring to the Decree of the Directorate General of Land Transportation 1996 and calculating the performance of planned public transportation to be able to determine the number of planned fleets referring to the Decree of the Directorate General of Land Transportation 2002. The results obtained are that the socio-economic characteristics that influence feeder transportation planning are age, occupation, income and travel characteristics that influence feeder transportation planning, namely travel destination and choice of transportation mode. The number of shelters will be planned at 8 points, each of which is located along the planning route. The planned number of fleets from Joyoboyo Terminal - Osowilangon Terminal is 13 fleets and from Osowilangon Terminal - Joyoboyo Terminal is 19 fleets.